2020
DOI: 10.26477/jbcd.v32i4.2914
|View full text |Cite
|
Sign up to set email alerts
|

Caries risk assessment of a sample of children attending preventive specialized dental center in Al Resafa, Baghdad

Abstract: Background: Young children’s oral health maintenance and outcomes are influenced by their parent’s knowledge and beliefs, which affect oral hygiene and healthy eating habits. This study aims at assessing caries risk in children aged 6 months to 6 years attending the Specialized Center of Preventive and Pediatric Dentistry Center at Al-Resafa sector in Baghdad. Materials and Methods: A cross-sectional study was conducted from 15 May – 15 June 2018, all children attended the center (80 children) were assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
1
3
0
Order By: Relevance
“…Most of the participants in this study had a high risk of caries (85%) while the remainder were in the moderate-risk group. These findings were similar to many previous studies [12,14,26]; however, there are some studies where the moderate-risk group was in the majority [25,27]. The recruitment of participants in this study was from a dental department where participants mostly came for dental treatment, which might be a plausible reason for the high risk of caries among participants.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most of the participants in this study had a high risk of caries (85%) while the remainder were in the moderate-risk group. These findings were similar to many previous studies [12,14,26]; however, there are some studies where the moderate-risk group was in the majority [25,27]. The recruitment of participants in this study was from a dental department where participants mostly came for dental treatment, which might be a plausible reason for the high risk of caries among participants.…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of dental caries is considerably lower in developed nations, which may be due to better living conditions, health awareness, application of fluorinated products, and preventive oral care programs [23][24][25]. Most of the participants in this study had a high risk of caries (85%) while the remainder were in the moderate-risk group.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast, Muhson et al . [ 32 ] reported moderate caries risk in 55.4% of their participants. A recent study conducted in Egypt[ 13 ] concluded that out of 52 participants, high and moderate risk children were equal (17 each).…”
Section: Discussionmentioning
confidence: 99%
“…The following criteria similar to the American Academy of Pediatric Dentistry (AAPD) Caries-risk Assessment Tool were used to determine a child's caries risk 35 :…”
Section: Study Design and Patient Populationmentioning
confidence: 99%